Pemberdayaan UMKM Dengan Model Bisnis Canvas Melaui Metode Participatory Learning And Action - Said Salim Dahda; Yanuar Pandu Negoro (SEWAGATI: Jurnal Pengabdian Masyarakat Indonesia, 2023)
MSMEs have a lot to contribute to increasing GDP and absorbing a large workforce. The development of technology and globalization opens up many business opportunities for larger MSMEs. With all the limitations and challenges, MSMEs must also continue to develop business models. MSME in Sidayu sub-district, Gresik have not been able to determine the direction of their business development. By taking the theme of introducing and developing business models, it is hoped that it can answer the problems of MSMEs. The canvas business model has been widely studied and applied to MSMEs because this business model is easier to understand and create. By using the lecture method and Participatory Learning and Action (PLA) MSME business actors are expected to have the understanding and ability to create a canvas business model. Implementation of creating a business model canvas, MSME players learn many new things related to developing value, determining consumer needs, taking advantage of external opportunities, obtaining resources and generating better income. The actors' enthusiasm in asking questions and creating a business model canvas about their MSMEs is an indicator of participants' understanding in participating in this activity.